MANAGING LEPTOSPIROSIS AS A PUBLIC HEALTH ISSUE: THE BURDEN OF RENAL AND HEPATIC INVOLVEMENT - L S M Waidyasuriya; KKS Chathurangani; LHMRL Ambillapitiya; D D Wickramaratna; JMKB Jayasekara (The Indonesian Journal of Public Health, 2026)
Introduction: Leptospirosis is a zoonotic infection that is found worldwide, mainly resulting in hepatic and renal complications. The occurrence of acute kidney injury (AKI) in leptospirosis varies from 40-60%, with a mortality rate of 22%. Aims: Identifying potential risk factors and assessing incidents of AKI and liver involvement are useful for managing comorbidities and mortality. Methods: A prospective cross-sectional study including one hundred and three clinically confirmed leptospirosis patients admitted to the Teaching Hospital, Rathnapura, Sri Lanka. An interviewer-administered questionnaire and medical records were used to collect data. Biochemical and hematological investigations were performed on admission and at discharge. Results: Farming (30.7%) and mining (31.8%) were the most common occupational exposures. The majority had cuts or bruises and had also been exposed to floodwater or contaminated water. The mean age was 45.5 ± 15.96 years, and most (94.2%) were males. AKI was observed in 26.2% (KDIGO criteria), and liver involvement in 28.16% (National Guidelines of Leptospirosis). Significant increases in hematological and biochemical parameters were observed in AKI patients compared to non-AKI patients (p<0.001). Similar observations were presented in patients with liver involvement compared to those without. Conclusion: Both AKI and liver involvement were observed in 29.6% of the population. Mining and agricultural involvement were identified as the main risk factors for leptospirosis. It is recommended that individuals refrain from entering the field if they have wounds and wear protective footwear before engaging in high-risk occupations.